Analysis of Critical Thinking Ability Reviewed from Adversity Quetient and Self-Confidence Through Problem Based Learning - Aminah, Nursaodah; Mohammad Asikin; Sugiman (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
Ability think critical is very important owned students, because think critical used for solve problem and become consideration when taking valid decision. Ability think critical must accompanied with aspect psychology For can finish problem with Good. Trust self and Adversity Quotient is one of necessary factors? for optimizing abilities possessed? student. Ability think critical can improved with a learning model Problem Based Learning (PBL) because pattern learning student centered which emphasizes student For role active with given something problems at the start purposeful learning? For compile knowledge students, and develop Skills think student in solution problem. Focus study This is analyze ability think critical reviewed from Adversity Quetient and trust self student through the Problem Based Learning model. Research methods used in the research This is method Systematic Literature Review (SLR). With method This identify, study, evaluate, and interpret existing research.? Based on study literature, PBL models can increase ability think critical student reviewed from Adversity Quotient and trust self student. Brave student? take it is the decision that can be made increase ability think critical, so student must own trust tall and brave?? try For can finish the problem It means student own intelligence Adversity Quotient